Ambiguities and Their Role in Constructing Stylistic Connotation: A Reading in Ahmed Zeki Abo Shadi’s Alyanbu’a Poetry - Ali Munim, Rania ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Previously and currently, the researcher had been interested in talking about ambiguities in the Arabic grammar. They realized their connotations and purposes. They had revealed their role in generating meanings and connecting the parts that create the textual structure as a form and connotation. Ambiguities means the elements that lack to a sign in between or a link such as pronouns, demonstrative nouns, a linking noun or adverbs. Recently, it focused on pronouns, demonstrative nouns, and linking nouns because they are ambiguous in the poetry of Ahmed Zekis especially in his poetic work Alyanbu’a. However, the question raises itself how the ambiguities contributed in constructing the connotation in the poetry of Ahmed Zeki and how it revealed the viewpoints and connotations that the poet tries by using these elements.